Pengaruh Pendidikan Kesehatan Dengan Ceramah Menggunakan Media Audiovisual Terhadap Peningkatan Pengetahuan Wus (Wanita Usia Subur) Dalam Pemilihan Kontrasepsi Iud (Intra Uterine Device) Di Desa Manjung Kecamatan Sawit Kabupaten Boyolali - Ratnawati, Ida Nurul; , Giat Purwoatmodjo, SKM., M.Kes; , Tanjung Anitasari I.K., SKM., M.Kes (2016)
The low use of contraceptives IUD is caused by various factors, one of which is the low level of knowledge. One of the ways that can be used to increase knowledge of WUS (women of fertile Age) about the IUD contraception is health extension with audiovisual media. The program guidance about contraceptives IUD will hopefully add to the knowledge of WUS about contraceptives IUD so that the number of participants KB IUD will also increase. The method was ued in this Quasi experimental design with Pretest-Posttest approach with a Control Group. The population of the research was the fertile Age Women aged 20-49 totaled 385. Total sample research as much as 70 sample, 35 samples for treatment group and 35 samples for the control group. Statistical analysis using T-test. The results showed: 1) there is no significant difference in levels of knowledge WUS about contraception IUD before and after the granting of health education in the control group (p=0,141>0.05). 2) there is a difference significant levels of knowledge about contraceptives IUD after the WUS are given health education between the control group and treatment group (p=0.000<0.05).